A case of lymphangioleiomyomatosis with multiple angiomyolipomas in the kidneys: a case report - How, Soon Hin; Sa'at@Yusof, Azlin; Pang, Yong-Kek; Liam, Chong-Kin (University of Malaya Medical Centre, 2006)
Lymphangioleiomyomatosis (LAM) is a rare disease. The reported prevalence is around one per million in the West but the exact prevalence in Asia is unknown. It affects primarily young women of reproductive age, with a mean age of onset at 34 years. The disease is characterised by an abnormal proliferation of smooth muscle-like cells that grow over a course of time to obstruct airways, lymphatic and blood vessels. We report a case of LAM in a young woman who presented with a spontaneous pneumothorax. Computed tomography scan of the thorax and abdomen showed homogenous thin-walled cystic lesions with normal intervening lung parenchyma and multiple lesions in her kidneys with Hounsfield units similar to that of fat.